Errors on the relative marker where: evidence from an EFL learner corpus - Supakorn Phoocharoensil, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The present study was aimed at investigating Thai EFL learners’ grammatical errors on their use of the relative marker WHERE. The data were collected from undergraduate students’ writings, which represent intermediate learner English, in Thai Learner English Corpus (TLEC).The findings indicate that the participants experienced the greatest difficulty using WHERE, i.e., as if it were functioning as a noun or noun phrase, which apparently emanates from learners’ overgeneralization. In comparison to the results of Phoocharoensil (2012), it seems that a great number of actual errors evidenced by the corpus-based data do not correspond to those found previously. In particular, the errors such as pronoun retention, preposition addition, and non-adjacency of RC to the head, which were prevalent in the past study, evidently occur with far lower frequency in the current study. This probably suggests that such problems reported in the past research may be due to limitations of the elicitation technique, i.e., a sentence combination task.